1997
DOI: 10.1007/s11663-997-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

Wall-to-bed heat transfer in a circulating fluidized bed for the reduction of iron ore particles

Abstract: A model is presented that describes the wall-to-bed heat transfer in a circulating fluidized bed (CFB) used for the prereduction of iron ore in the smelting-reduction iron-making process. The model incorporates the core-annulus type flow structure and the wall emulsion layer growing downward along the surface. Model predictions showed good agreements with measured data taken from the literature. The hydrodynamic behavior near the wall surface was able to be properly described by the core-annulus flow structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…And it has been observed in practice especially for fine iron oxide particles. [18][19][20][21] Hence, it is assumed that the mass transfer resistance of gases from the bulk to the surface can be neglected. Thurnhofer 18) conducted microscopical analyses of polished sections of reduced iron ore fines and observed that a high amount of pores were spread through the entire fine.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…And it has been observed in practice especially for fine iron oxide particles. [18][19][20][21] Hence, it is assumed that the mass transfer resistance of gases from the bulk to the surface can be neglected. Thurnhofer 18) conducted microscopical analyses of polished sections of reduced iron ore fines and observed that a high amount of pores were spread through the entire fine.…”
Section: )mentioning
confidence: 99%
“…So pore diffusion is not limiting the reduction. Based on these assumptions and observations, Hahn,19,20) Thurnhofer,…”
Section: )mentioning
confidence: 99%
“…Equation [13] indicates that the fines have smaller residence times than the coarse because of larger K(d pi ) values for the fines. In the extreme, for fine particles, where K(d pi )…”
Section: Residence Time Distributionmentioning
confidence: 99%
“…Recently, Hahn et al [11,12,13] bed (CFB) for prereduction of iron ores. Their model incorporates hydrodynamics, reduction kinetics, and heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation